Hospital admissions due to ambulatory care sensitive conditions among children by age group and health region - Kelly Holanda Prezotto; Maria Marta Nolasco Chaves; Thais Aidar de Freitas Mathias (SciELO, 2015)
OBJECTIVE to describe hospital admissions for ambulatory care sensitive conditions in children under five years of age in the State of Paraná, Brazil by condition type, age group and health region. METHOD a temporal ecological study was conducted using data from the Unified Health System Hospital Information System for the period 2000 to 2011. Conditions were grouped in accordance with the list of ambulatory care sensitive conditions in Brazil. RESULTS there was an increase in the rate of admissions for ambulatory care sensitive conditions in all age groups in 50% of the health regions, with a marked increase in children under the age of one. Pneumonia, gastroenteritis and asthma were the main causes of admissions. There was an increase in the proportion of overall admissions accounted for by pneumonia and gastroenteritis. CONCLUSION the increase in admissions reveals the need for actions to improve access to primary healthcare and provide effective treatment of the main ambulatory care sensitive conditions in order to prevent hospital admissions among children.